Efficacy of feline anti‐parvovirus antibodies in the treatment of canine parvovirus infection. (31st March 2017) - Gerlach, M.; Proksch, A. L.; Unterer, S.; Speck, S.; Truyen, U.; Hartmann, K.
Abstract : Objective: This prospective, randomised, placebo‐controlled, double‐blinded study aimed to evaluate efficacy of commercially available feline anti‐parvovirus antibodies in dogs with canine parvovirus infection. Methods: First, cross‐protection of feline panleukopenia virus antibodies against canine parvovirus was evaluated in vitro. In the subsequent prospective clinical trial, 31 dogs with clinical signs of canine parvovirus infection and a positive faecal canine parvovirus polymerase chain reaction were randomly assigned to a group receiving feline panleukopenia virus antibodies (n=15) or placebo (n=16). All dogs received additional routine treatment. Clinical signs, blood parameters, time to clinical recovery and mortality were compared between the groups. Serum antibody titres and quantitative faecal polymerase chain reaction were compared on days 0, 3, 7, and 14. Results: In vitro, canine parvovirus was fully neutralised by feline panleukopenia virus antibodies. There were no detected significant differences in clinical signs, time to clinical recovery, blood parameters, mortality, faecal virus load, or viral shedding between groups. Dogs in the placebo group showed a significant increase of serum antibody titres and a significant decrease of faecal virus load between day 14 and day 0, which was not detectable in dogs treated with feline panleukopenia virus antibodies. Clinical Significance: No significant beneficial effect of passively transferred feline anti‐parvovirus antibodies in the used dosage regimen on the treatment of canine parvovirus infection was demonstrated.